Predictors of patent length of stay post-stroke in a sub-acute rehabilitation setting in Gauteng - Bijl, Thea (My University, 2017)
Background Stroke is the main cause of disability in South Africa. Patients who have a stroke require effective rehabilitation to achieve optimal function. Patient progress can be monitored with standardised outcome measures such as the Functional Independence Measure (FIM). This data along with other demographic and clinical data may be useful in making predictions about patients’ functional outcomes and length of hospital stay (LOS). As LOS is an important indicator of the cost of care for patients post-stroke, this information may be useful to all stakeholders involved in the care and rehabilitation process. Method A retrospective file review was done for 243 patients post-stroke who were admitted to a private, sub-acute rehabilitation facility in Gauteng between 1 January 2015- 31 January 2017. Patient functional ability was measured using the FIM. Demographic and clinical data of the patients were also recorded. Descriptive statistics were used to summarise the data. Median and range values were used to describe the sample, their functional outcomes and their LOS. To determine if there were differences in patient outcomes (FIM scores and LOS) one-way ANOVA were done. Multiple regression analysis was done to determine the predictive value of clinical, demographic and functional variables on LOS. Results The median admission and discharge FIM scores were 43 points and 75 points respectively, and the median LOS was 43 days. Only admission FIM score had an influence on both discharge FIM score and FIM change scores. With the stepwise multiple regression model, the following patient characteristics were found to be predictors of LOS: the presence of a premorbid psychiatric condition, impaired speech on admission, requiring additional oxygen support, the development of pneumonia and the admission FIM motor score. The overall variance predicted by the model was 26.3%. Admission FIM motor score was the strongest individual predictor of LOS in this study (41%). Conclusions Low admission FIM score has an influence on poor patient outcomes and is important in the prediction of LOS for patients post-stroke in a private, sub-acute rehabilitation facility in South Africa. Low functioning patients post-stroke stay longer in hospital and may require more resources to get them to functional levels. Other clinical variables may also influence LOS. Patients with speech impairments and those who require oxygen support on admission may require longer LOS to allow for more complete recovery. Patients who have a premorbid psychiatric condition or develop pneumonia have shorter LOS as they may not be able to participate effectively in rehabilitation or make adequate rehabilitation gains, leading to early discharge, or transfer back to an acute facility. Recommendations Study results may assist the facility to tailor its services to meet the specific needs of South African stroke patients. Being able to predict LOS on admission allows facility administrators to manage bed occupancy, human and clinical resources. Facilities may need to ensure that they are able to allocate enough beds to patients that need a longer LOS, ensure adequate numbers of therapists to manage the case-load and ensure early screening to prevent the development of complications (pneumonia). Low admission FIM motor scores may be used to motivate for additional funding and longer LOS from medical aid schemes. The short-term increase in costs in the interest of long-term savings may provide motivation for improved coverage for stroke patients requiring rehabilitation in South Africa’s private healthcare sector. High admission FIM motor scores may also be used as justification for shorter stays, earlier discharge and appropriate referral to out-patient therapy. All of which reduce the cost of care post-stroke. The findings of the study by the researcher will be sent to the rehabilitation facility in which the study was done and to South African journals for publication of the study findings, to disseminate them to South African therapists. Future studies should consider using regression analyses to determine predictors of functional outcome as well as LOS. Rehabilitation facilities should implement the use of more standardised outcome measures to improve the quality of clinical data collected at these facilities.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in partial fulfillment of the requirements for the degree of Master of Science in Physiotherapy by course work and research report. Gauteng, 2017